Pengaruh Capital Adequacy Ratio (Car), Bopo, Non Performing Financing (Npf), Dan Financing To Deposit Ratio (Fdr) Terhadap Return On Asset (Roa) Pada Bank Pembiayaan Rakyat Syariah Periode Januari 2011 - Desember 2015 - Yohana, Dhyas Funky; , Drs.Yuni Prihandi Utomo, MM (2017)
ABSTRACT The research aims at examining the effect of several variables, they are: Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Operational Cost Operational Income (BOPO: BiayaOperasionalPendapatanOperasional), and Financing to Deposit Ratio (FDR) toward Profitability (ROA) in Bank Pembiayaan Rakyat Syariah from January 2011till December 2015. The analysis of the research is regression. It employs Partial Adjustment Model (PAM), and Classical Assumption Test which is analyzed by using Quantitative Micro Software EViews. The finding of Partial Adjustment Model (PAM) test shows that variable CAR and FDR have no significant contribution toward ROA in the short and long term, on the contrary variable NPF and BOPO do. Whereas the result of Determination Coefficient indicates that correlation between Profitability (ROA) bank and the four free variables are 90, 18%. Keywords: CAR, BOPO, NPF, FDR, BPRS